3-Hydroxy-2-[(2-hydroxy-4,4-dimethyl-6-oxocyclohex-1-en-1-yl)(3-nitrop henyl)methyl]-5,5-dimethylcyclohex-2-en-1-one - Reddy, B.P.; Vijayakumar, V.; Sarveswari, S.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
Each of the cyclohexenone rings in the title compound, C23H27NO6, adopts a half-chair (envelope) conformation with the C atom carrying the methyl groups lying out of the plane defined by the five remaining C atoms; the O atoms lie to the same side of the molecule as the respective >C(CH3)(2) atoms. The hydroxy and carbonyl O atoms face each other and are orientated to allow for the formation of two intramolecular O-H center dot center dot center dot O hydrogen bonds. In the crystal, the presence of C-H center dot center dot center dot O contacts leads to the formation of supramolecular chains along the b axis. These aggregate into layers that stack along c.